Analisis Syariah Karateristik Produk Pru Cinta - Yusrizal Yusrizal; Anni Zuhro Syafrida Hasibuan (Economic Reviews Journal, 2022)
The quantity of halal insurance product studies has not been able to keep up with the growth of the sharia insurance market. This shows that there are still many sharia insurance products that are not in accordance with Islamic teachings. The use of sharia insurance policies must really be considered so that the halalness of the product is maintained. The mechanism for implementing Prudential's sharia insurance products will be discussed in this article (Pru Cinta). Carefully describes the application of pru love, which will then be compared with Islamic teachings. Prucinta's caution is not fully compliant with sharia standards, according to the study. Keyword : Analisys, Pru Cinta, Sharia Insurance